Oestrogen receptor transcripts associated with cervical human papillomavirus infection. Issue 3 (1st June 2002) - Shew, M L; McGlennen, R; Zaidi, N; Westerheim, M; Ireland, M; Anderson, S
Abstract : Objective: Studies have been inconsistent in establishing sex steroids as a risk factor for human papillomavirus (HPV) infections. This study was designed to determine whether cervical oestrogen receptors (as measured by oestrogen receptor transcripts) at the cervix would be associated with cervical HPV infections. Methods: In 175 women, ages 14–44, we tested for the presence of HPV DNA and oestrogen receptors transcripts at the cervix during routine pelvic examinations. All subjects completed a self administered questionnaire regarding sexual and menstrual histories. Results: 40% of the women (n=70) tested positive for HPV at the cervix. Of those women testing positive for HPV, 99% had detectable levels of Oestrogen receptors transcripts (n=69/70). HPV cervical infections were independently associated with presence of Oestrogen receptors transcripts (OR = 39.8, CI=4.4, 361.1) and greater numbers of sexual partners (OR=1.1, CI=1.01, 1.18). Conclusion: Women who expressed higher levels of oestrogen receptors transcripts were significantly more likely to have cervical HPV infection. These results demonstrate that Oestrogen receptors may play an important part in cervical HPV infections.